Legal Protection for Nightclubs Female Workers in Bali - Ni Nyoman Juwita Arsawati; Gde Made Swardhana; Diah Ratna Sari Hariyanto; Dewi Bunga (Sriwijaya Law Review, 2024)
This study aims to identify, analyse, and find the risks and legal protections for female workers at nightclubs in Badung, Bali, Indonesia. Through empirical legal research, based on the study's results, it can be found that there are many risks faced by female workers who work at nightclubs. The risks faced by female workers at nightclubs in Badung, Bali, can include health risks (physical and mental/psychological), safety risks, risks of victimisation (becoming victims of criminal acts), getting a negative prejudice from the community, being ostracised, and the risk of falling into prostitution and drug abuse. Legal protection for female workers in nightclubs has yet to be implemented optimally. Many rights and protections are owned by women who work in nightclubs, but nightclubs cannot reach them. There are still many violations of the law against female workers. Management does not provide rights for night workers in accordance with the provisions of the Manpower Act because these workers are not included in the Labor Union. The legal consequences for women workers at night entertainment sites need better legal protection, especially in the context of the labour force. Stigmatising women employees at night recreation sites as prostitution workers also weakens protection for them.Women workers do not fight for their rights because they do not have much understanding of their rights.